Cement Stabilized Structural Foundation Lateritic Soil with Bone Ash Powder as Additive - Adetayo, O. A.; Amu, O. O.; Ilori, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Investigation on the potentials of bone ash powder on cement stabilized structural foundation was carried out in this paper. The aim of the study was to discover local waste material as complement for cement to reduce construction cost. Three soil samples were collected from different borrow pits in Ile-Ife and Ibadan, Nigeria called sample A, B and C. Preliminary tests such as the natural moisture content, specific gravity, grain size analysis and Atterberg’s limits were performed on the samples at their natural states and when stabilized at the condition of 8, 8 and 6% cement for samples A, B and C respectively. Engineering tests such as compaction, California bearing ratio (CBR) and undrained traixial were also performed on them at their natural states, when stabilized with optimum cement and when bone ash powder (BAP) was introduced at 2, 4, 6 and 8% to the samples. The results of the engineering tests showed that BAP increased the maximum dry density (MDD) of all the samples. With the optimum cement content kept at 8% for samples A and B and 6% for sample C, the values increased from 1687.89 to 2219.05 kg/m3 and 1634.12 to 2174.71 kg/m3 at 4% in samples A and B respectively and 1521.59 to 1620.70 kg/m3 in sample C at 2% BAP content. The unsoaked CBR values of all the cement stabilized samples dropped with BAP contents. The values dropped from 4.79 to 1.79%, 3.88 to 2.31% and 4.84 to 2.43% respectively in samples A, B and C. However, the shear strengths of samples A and B increased from 604.77 to 740.09 kN/m2 and 317.73 to 616.05 kN/m2 respectively. It was therefore concluded that BAP is not an effective additive on cement stabilized structural foundation soil, except in the compaction and shear strength characteristics.